The response of two Tethyan carbonate platforms to the early Toarcian (Jurassic) oceanic anoxic event: environmental change and differential subsidence - Woodfine, R; Jenkyns, H; Sarti, M; Baroncini, F; Violante, C (2008)
Chemostratigraphic analyses (87Sr/86 Sr, δ13 Ccarb) of limestones from two Jurassic platform-carbonate sequences in Italy (Trento and Campania-Lucania Platforms) illustrate previously established trends found in pelagic sediments and skeletal carbonates from biostratigraphically well-calibrated sections elsewhere in Europe. Chemostratigraphic correlations between the platform-carbonate successions and appropriate intervals from well-dated reference sections allow the application of high-resolution stratigraphy to these shallow-water peritidal carbonates and, furthermore, elucidate the facies response to the Early Toarcian Oceanic Anoxic Event (OAE). Lower Jurassic (Toarcian) levels of the western Trento Platform (Southern Alps, Northern Italy) contain spiculitic cherts that appear where rising carbon-isotope values characterize the onset of the OAE: a palaeoceanographic phenomenon interpreted as driven by increased nutrient levels in near-surface waters. There is a facies change to more clay-rich facies at the level of the abrupt negative carbon-isotope excursion, also characteristic of the OAE, higher in the section. The Campania-Lucania Platform (Southern Apennines, Southern Italy) records a change to more clay-rich facies where carbon-isotope values begin to rise at the beginning of the OAE but the negative excursion, higher in the section, occurs within oolitic facies. Although, in both examples, the Early Toarcian OAE can be recognized by a change to more clay-rich lithologies, this facies development is diachronous and in neither case did the platform drown. Although the Trento Platform, in the south-west sector studied here, was adversely affected by the OAE, it did not drown definitively until Late Aalenian time; the Campania-Lucania Platform persisted throughout the Jurassic and Cretaceous. Differential subsidence rates, which can be calculated using comparative chemostratigraphy, are identified as a crucial factor in the divergent behaviour of these two carbonate platforms: relatively fast in the case of the Trento Platform; relatively slow in the case of the Campania-Lucania Platform. It is proposed that where water depths remained as shallow as a few metres during the OAE (Campania-Lucania Platform), dissolved oxygen levels remained high, nutrient levels relatively low and conditions for carbonate secretion and precipitation remained relatively favourable, whereas more poorly ventilated and/or more nutrient-rich waters (Trento Platform) adversely influenced platform growth where depths were in the tens of metres range. The stage was thus set for drowning on the more rapidly subsiding western margin of the Trento Plateau and a pulse of oolite deposition post-dating the OAE was insufficient to revitalize the carbonate factory. © 2008 The Authors. Journal compilation © 2008 International Association of Sedimentologists.